Digital sequence information is changing the way genetic resources are used in agricultural research and development: implications for new benefit-sharing norms - Hamilton, Ruaraidh S.; Halewood, Michael; López Noriega, Isabel; Rouard, Mathieu; Tiambo, Christian K.; Azevedo, Vania; Bhattacharjee, Ranjana; Cuéllar, Wilmer Jose; Gisel, Andreas; Hearne, Sarah Jane; Heider, Bettina; Hendre, Prasad; et al. (CGIAR Initiative on Genebanks, 2022)
This paper analyses the ways in which CGIAR Centers use digital sequence information (DSI) in their efforts to conserve and sustainably utilize the world’s most important crop and livestock genetic diversity. The paper then reflects on which of the benefit-sharing options currently under consideration by the Contracting Parties to the CBD (and the versions of those options that must be considered by the Governing Body of the Plant Treaty and the UN FAO Commission on Genetic Resources for Food and Agriculture) would provide effective policy support for the continued use of DSI in agricultural research and development in the future.